2019
DOI: 10.1002/mus.26690
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal reliability of outcome measures in patients with Duchenne muscular dystrophy

Abstract: Introduction: The definition of reliable outcome measures is of increasing interest in patients with Duchenne muscular dystrophy (DMD). Methods: In this retrospective study, we analyzed the longitudinal reliability of clinical and radiological endpoints in 29 ambulant patients with DMD. Clinical outcome measures included motor function measure (MFM) and timed function tests, while quantitative MRI data were mean fat fraction (MFF) and T2 relaxation time of thigh muscles. Statistical analysis was based on 3-, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Although previous interventional studies had very small sample sizes, it is generally hypothesized that imaging may be able to detect subclinical disease progression in advance of changes in functional performance. Furthermore, quantitative MRI measures may be more sensitive than functional measures in tracking disease progression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous interventional studies had very small sample sizes, it is generally hypothesized that imaging may be able to detect subclinical disease progression in advance of changes in functional performance. Furthermore, quantitative MRI measures may be more sensitive than functional measures in tracking disease progression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated correlations between functional tests and imaging [14][15][16][17][18][19] and a systematic review reported correlations between MRI measurements and motor function, with the strongest correlations using quantitative MRI measurements such as fat fraction or mean T2 [20]. Furthermore, recent retrospective analyses from natural history studies have shown that MRI fat fraction and T2 measures in the vastus lateralis and biceps femoris long head were among the fastest progressing biomarkers to predict future functional decline in boys with DMD [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report to present detailed data on improved motor function and relevant symptoms in an adult patient with childhood-onset HPP by asfotase alfa therapy. Drug efficacy was clearly demonstrated using multiple test batteries already adopted in DMD clinical trials due to no established testing for motor function in HPP [ 8 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle fat fraction (FF) can be quantified reliably using Dixon chemical-shift magnetic resonance imaging (MRI) or MR spectroscopy (MRS), and is considered a promising biomarker in muscular dystrophies (3,4). In Duchenne muscular dystrophy (DMD), FF increases within 12 months (5,6), predicts change in function and clinical milestones (7,8), and reduces sample sizes needed to detect a treatment effect compared to functional outcome measures (5,9,10). Quantitative muscle MRI also proved more sensitive to detect changes than functional measures in other, slowly progressive, neuromuscular diseases like FKRP related limb girdle muscular dystrophy R9, GNE myopathy, and Charcot Marie Tooth 1A (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%